2012
DOI: 10.2138/am.2012.4041
|View full text |Cite
|
Sign up to set email alerts
|

Europium oxidation state and local structure in silicate glasses

Abstract: Europium LIII-edge XAS spectra were recorded for silicate glasses of different compositions, quenched from melts equilibrated at different oxygen fugacity (fO2). The Eu XANES spectra vary systematically with glass composition and with fO2 (–log fO2 ~0 to ~11.9) indicating changes in the Eu oxidation state. The intensity of the main peaks on the absorption edges were quantified and used to determine the Eu2+/(Eu2++Eu3+) ratio. All the Eu-bearing glasses synthesized in air show the prevalent presence of Eu3+ but… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
20
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 63 publications
4
20
0
Order By: Relevance
“…Introduction of nitrogen into the glass matrix after the nitridation probably changes the local environment of the optical centers causing a decrease of lifetime, but it is important to note that still just one distribution band over the lifetimes is observed (see Table 2), and there are not further evidences of various Eu 3+ sites in the studied glasses. These results are in agreement with previous studies on simplified and multicomponent silicate glasses [7,29], where it was observed that the bulk chemistry does not produce strong modifications on the Eu 3+ local environment.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Introduction of nitrogen into the glass matrix after the nitridation probably changes the local environment of the optical centers causing a decrease of lifetime, but it is important to note that still just one distribution band over the lifetimes is observed (see Table 2), and there are not further evidences of various Eu 3+ sites in the studied glasses. These results are in agreement with previous studies on simplified and multicomponent silicate glasses [7,29], where it was observed that the bulk chemistry does not produce strong modifications on the Eu 3+ local environment.…”
Section: Discussionsupporting
confidence: 93%
“…Previous studies on borophosphate, boroaluminate, and boroaluminosilicate glasses [3][4][5] shown that the optical basicity of the glasses affects the Eu oxidation state (higher the optical basicity, higher is the amount of oxidized species). In turn, it is also possible to correlate the NBO/T parameter (non-bridging oxygen over tetrahedra) to the Eu redox ratio, as described for simplified and multicomponent silicate glasses [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…However, it is apparent that the glass structure, in particular, the Al 3+ ions play an important role to the Eu–O chemical bonds. XAFS measurements were used to verify the structures of Eu 3+ ions . After carrying out extraction of the EXAFS signals from experimental absorption spectra, the radial distribution functions were obtained from Fourier transformation of the k 3 ‐weighted EXAFS oscillation curves, k 3 χ(k), in the k ‐space region from about 2 to 12 Å −1 , where k is the magnitude of the wave vector of photoelectron; the calculated distribution curves around the Eu atoms are shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The Eu threshold energy was taken as the first maximum of the first derivative of the spectra, whereas peak positions were obtained by calculating the second derivative of the spectra. Eu data analysis was carried out by following the procedure described in Cicconi et al (2012). In brief, the peaks relative to Eu 2+ and Eu 3+ can be fitted by a combination of pseudo-Voigt (pV) and arctangent (atg) functions to simulate the XANES spectra (i.e., Takahashi et al 2005;Cicconi et al 2012).…”
Section: Samples and Analytical Techniquesmentioning
confidence: 99%
“…Eu data analysis was carried out by following the procedure described in Cicconi et al (2012). In brief, the peaks relative to Eu 2+ and Eu 3+ can be fitted by a combination of pseudo-Voigt (pV) and arctangent (atg) functions to simulate the XANES spectra (i.e., Takahashi et al 2005;Cicconi et al 2012). The pV and atg functions simulate the resonance peak and the absorption edge step, respectively.…”
Section: Samples and Analytical Techniquesmentioning
confidence: 99%